The influence of organizational culture, work discipline and work motivation on performance State Civil Apparatus (ASN) Medan Trade - Syamsul Bahri Surbakti; Akman Daulay; Sinto Sinto; Mia Anjalika Manik (ProBisnis : Jurnal Manajemen, 2022)
This study analyzes the relationship between Organizational Culture and Work Motivation on the Performance of State Civil Apparatus (ASN). The statistical method used is multiple regression with a quantitative descriptive approach using the classical assumption test first.The population of this research is the State Civil Apparatus of the Medan City Trade Service as many as 74 respondents which are calculated from the number of workers in the Medan City Trade Office, the number of samples in the study is 74 people. Meanwhile, simultaneously both Organizational Culture (X1), Work Discipline (X2) and Work Motivation (X3) have a positive and significant effect on the Performance of the State Civil Apparatus of the Medan City Trade Service (Y). The results of this study indicate that partially the Organizational Culture variable (X1), Work discipline (X2) andWork Motivation (X3) have a positive and significant effect on the Performance of the State Civil Apparatus of the Medan City Trade Service (Y)